Allogeneic stem cell transplantation as part of front line therapy for Mantle cell lymphoma. (17th December 2018) - Rule, Simon; Cook, Gordon; Russell, Nigel H.; Hunter, Ann; Robinson, Stephen; Morley, Nick; Sureda, Anna; Patrick, Pip; Clifton‐Hadley, Laura; Adedayo, Toyin; Kirkwood, Amy; Peggs, Karl S.
Summary: Mantle cell lymphoma (MCL) is an aggressive form of non‐Hodgkin lymphoma that remains incurable for the majority of patients. Allogeneic stem cell transplantation (alloSCT) produces long‐term disease‐free remissions for around 30–40% patients, however it is reserved for the treatment of relapsed disease. This study examined the use of front line transplantation for young patients in an attempt to improve outcomes. Twenty‐five patients received an alloSCT using BEAM [BCNU (carmustine), etoposide, cytarabine, melphalan)‐Campath conditioning following permissive induction therapy from both related and unrelated donors. This was a multi‐centre prospective trial. Twenty‐four of 25 patients engrafted with no non‐relapse mortality events by day 100. With a median follow‐up of 60·5 months, there have been six deaths (3 from MCL). The progression‐free survival (PFS) and overall survival were 68% and 80% at 2 years and 56% and 76% at 5 years. PFS was very similar for both sibling and unrelated transplants and there was no difference in PFS between patients with respect to remission status prior to transplantation. Nine (38%) patients experienced acute graft‐versus‐host disease (GVHD) and 14 (58%) experienced chronic GVHD, of which 8 were extensive. Front line alloSCT is feasible but should only be considered for patients at high risk of early progression following conventional therapy.